PEMANFATAAN REMITANSI EKONOMI DAN SOSIAL DI KALANGAN BURUH MIGRAN PEREMPUAN (STUDI KASUS: DESA PENGGALANG DAN WELAHAN WETAN, KECAMATAN ADIPALA, KABUPATEN CILACAP, PROVINSI JAWA TENGAH) - Octaviani, Laila (Faculty of Social Science, Universitas Negeri Semarang, 2015)
This study on the Economic and Social Remittance Utilization Among Migrant Workers At Village Penggalang and Welahan Wetan, District Adipala, Regency of Cilacap, yet maximize the utilization of optimal economic remittances in improving the welfare of the family after returning to their hometown. The existence of a patriarchal system and stigma about migrant workers women as rural women, primary school graduates and former Housemaid, which further weaken their position in the family structure and society. During this time, the process of international migration female migrant workers do not just talk the problem over the issue of migration remittance economy and its impact on development that they forget aspects more substantial, namely social remittances. In this case, the process of international migration that they receive in the form of economic and social remittances can be a means not only to empower themselves by raising social position in the family and society and can also empowering environment. The problem is how to position himself (female migrant workers) post back to the area of origin of the family and community structures. As well as how to use the remittance economy and sosialdiperoleh women migrant workers in order to improve the welfare of the family after returning to their home areas. Therefore, this study aims to position the female migrant workers after returning to the area of origin of the structure of families and communities through the use of economic and social remittances obtained, as well as to analyze and apply the theory / concept of anthropology.The method used in this study is a qualitative ethnographic method with techniques of data collection is done by in-depth interviews, observation and documentation study participation to all informants related to the utilization of remittances in the economic and social Penggalang and Welahan Wetan village, District Adipala, Regency of Cilacap.Results showed that the remittances of economic and social obtained the female migrant workers Village Penggalang and Welahan Wetan, District Adipala, Regency of Cilacap be used optimally so that women migrant workers and their families become more empowered again, which is influenced by several factors, namely 1) female migrant workers destination country; 2) the experience gained from the country of destination; 3) the role of Lakpesdam NU Cilacap along with Tifa Foundation and BNP2TKI, The Empowerment of Women Migrant Workers and Their Families in the Place of Origin with funding JSDF World Bank as well as all relevant stakeholders both government and non-government at national and local level by involving through support to development of Community-BasedOrganization (CBO) as one of the pillars of the protection of migrant workers in the area of origin. And the involvement of relevant agencies in protecting migrant workers, especially women in Cilacap, the formulation of the Regional Regulation Cilacap District No. 7 of 2014 on the Protection of Indonesian Workers Cilacap and Regent Decree Cilacap No. 465.2 / 138/29 / Year 2013 regarding the Establishment Group Family Development Workers Indonesia working in Cilacap.